Teaching how to make specific historical causal claims (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The theme of the conference is a celebration of history teaching in the 350th year of schooling in South Africa. A lot of developments have happened during with regard to the teaching and understanding of history as a subject. In order to appreciate these developments in the classroom, students should be able to make specific historical claims. Making specific historical causal claims of the form ‘A caused that B’ is one of the most important things that a person learns. However, the making of causal claims is not confined to the teaching and learning context. School children of whatever age, are in a position of making specific historical causal claims, and do this in varying degrees of skill and standards. The purpose of effective history teaching should be to develop in students a deeper understanding of historical processes. Whilst historical claims can be made about all sorts of things, in this paper, attention will be confined to those claims that have direct relevance to the teaching and learning situation in history. The paper identifies critical issues that need to be considered to make this succeed in the history classroom.
Keywords: history teaching; historical claims; historical causal claims